The Inexhaustible Right to Exclude Reproduction Doctrine - Rogers, Eric J. (Science and Technology Law Review, 2013)
The seed industry uses the combination of patent law and contract law to limit the use of patented seeds placed into the stream of commerce. This practice implicates both patent exhaustion and patent misuse. With respect to patent exhaustion, there is a dilemma: how to protect patent owners with self-replicating products while maintaining the principle of patent exhaustion. In Bowman, the Supreme Court offered a solution to the dilemma by creating a new technology-specific doctrine of patent exhaustion: the ‘inexhaustible right to exclude reproduction.’ This new doctrine simply sets the confines of the patent grant to include reproduction of an organism as infringing upon the patentee’s right to make and largely fulfills the goals of patent exhaustion and patent misuse. However, the inexhaustible right to exclude reproduction doctrine creates patent rights that move forever with self-replicating products based on how the product is used. These property restrictions that ‘run with the seeds’ might catch the unwary downstream user, inhibit trade and add transaction costs. The creation of inexhaustible patent infringement liabilities with regard to patented organisms currently results in little harm to the public. However, as the volume of sales of patented organisms increases, this doctrine will pressure downstream users to expend increasing efforts in considering patent rights before acquiring any self-replicating property for the purpose of reproduction.